PENGGUNAAN METODE DISCOVERI UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DI KELAS V SD NEGERI 02 MUARA PANAS KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - Fidrawati Fidrawati (Pedagogi: Jurnal Ilmu Pendidikan, 2015)
Based on the background of the problem so the researcher can make edification of the problem: the students are not active in study, so they think IPA subject is not interesting subject, and the teacher is the first information but the students are only listen it, to improve the students ability in IPA subject need give some competence for their, so it can become the students study IPA subject with active, creative and can study their environment. The method of Discovery is one of the method of learning can be used in IPA subject. In using this method the students are guldens by teacher in find the concept of the subject wish some ways; observation, identification and explanation the conclusion. This method have some technique, there is the problem that will be solved, explanation what class are they for example the students class five prepare the tool based on the students need in doing activities, thinking the citizen must be explanation to make the students self confidence. This research is done in semester two class five at SDN 02 Muara Panas, 2014/2015. This research divided two cycles, in this research the researcher has collaboration with other teacher as observation. At that time in the class the researcher as IPA teacher. With topic “Identification of the plane in photosynthesis” and other teacher as observer at that time. These researchers started with observation; that is observation of the IPA learning in class five at SDN 02 Muara Panas. This research has collaboration with other teacher as observer to using the method of discovery in IPA subject. Based on explanation and research evaluation in chapter four, the conclusion of the research: in order that IPA subject evaluation can improve needed good situation, ways and method of learning. To make the student study IPA subject with active, both imaginations, hearing and observing. On the students evaluation in using the method of Discovery in learning process is better than using the method of speech. At class five SDN 02 Muara Panas it can observe from the students evaluation as 6.16 before the research and after of the research the students evaluation as 8.95 in this PTK we can get the conclusion that using this method the teacher hope can guide the students and as facilitator of all students and can make the students active in the group.